A case of FN1‐fused calcified chondroid mesenchymal neoplasm of the hand with novel FGFR3 partner gene. Issue 4 (23rd December 2022) - Georgantzoglou, Natalia; Shen, Guomiao; Jour, George; Linos, Konstantinos
Abstract: Calcified chondroid neoplasms with FN1::FGFR1 or FGFR2 fusions constitute a recently described category of mesenchymal neoplasms mostly encountered in the extremities and temporomandibular joint. Herein, we report a case of FNI1 ‐fused calcified chondroid neoplasm of the hand with a novel FGFR3 fusion partner. The tumor exhibited a multilobulated growth pattern composed of epithelioid cells embedded in abundant stroma with myxoid, chondroid, and fibrous areas and scattered osteoclast‐like giant cells. RNA sequencing revealed an in‐frame fusion between Exon 31 of FN1 and Exon 3 of FGFR3, which was subsequently confirmed by reverse transcription‐polymerase chain reaction. Our findings expand on the spectrum of potential fusion partners in FN1 ‐fused calcified chondroid neoplasms.